TRIGONOMETRY - Abdullayev Nurbek Shuhrat og'li; Ro'ziqulov Sa'dulla Egamnazar o‘g‘li; Yoʻldoshev Bekmirza Shuxrat oʻgʻli (American Journals Publishing, 2024)
This article will talk about what scientific research scientists have done in ancient times in the formation of trigonometry.
Keywords: Trigonometry, triangle, diameter, segment, sine, cosine, radian.